2022
DOI: 10.19109/limas_pgmi.v3i1.12971
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Nilai Pendidikan Karakter Dalam Kegiatan Ekstrakulikuler Drumband Siswa Sekolah Dasar Negeri 2 Gumawang

Abstract: Penelitian ini dilatar belakangi oleh permasalahan terkait Analisis Nilai-nilai Pendidikan Karakter dalam Kegiatan Ekstrakulikuler Drumband Siswa di Sekolah Dasar Negeri 2 Gumawang. Tujuan dari penelitian ini yaitu (1) Untuk mengetahui nilai karakter yang terkandung dalam ekstrakulikuler Drumband siswa. (2) Untuk mengetahui pelaksanaan kegiatan ekstrakulikuler Drumband siswa. (3) Untuk mengetahui kendala dalam pelaksanaan kegiatan esktrakulikuler Drumband siswa. Penelitian ini menggunakan penelitian kualitatif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Kegiatan drumband dapat membentuk sikap toleransi, kerjasama, disiplin, kreativitas dan cinta tanah air. Hal tersebut terbentuk dari latihan berkesinambungan dan pembelajaran lagu-lagu nasional yang dilantunkan dalam permainan drumband (Puspitasari et al, 2022). Berdasarkan laporan praktik pengalaman lapangan, Indrawati (2015) mengatakan bahwa adanya pendampingan drumband yang dilakukan oleh guru maupun pelatih dimaksudkan untuk memberikan semangat dan motivasi kepada anak-anak agar giat berlatih.…”
Section: Latar Belakangunclassified
“…Kegiatan drumband dapat membentuk sikap toleransi, kerjasama, disiplin, kreativitas dan cinta tanah air. Hal tersebut terbentuk dari latihan berkesinambungan dan pembelajaran lagu-lagu nasional yang dilantunkan dalam permainan drumband (Puspitasari et al, 2022). Berdasarkan laporan praktik pengalaman lapangan, Indrawati (2015) mengatakan bahwa adanya pendampingan drumband yang dilakukan oleh guru maupun pelatih dimaksudkan untuk memberikan semangat dan motivasi kepada anak-anak agar giat berlatih.…”
Section: Latar Belakangunclassified
“…Instilling character values in students is able to make them as superior human resources as the nation's next generation. The purpose of character education is to develop and shape the ability of students to sort out good and bad decisions, maintain good values and realize goodness in life wholeheartedly, oriented to science and technology as a whole by faith and piety to God Almighty which is based on the ideology of Pancasila [4][5][6][7]. As with the direction and purpose of character education, there are various kinds of characters that need to be realized in education, including the character of self-confidence [8,9] and the character of responsibility [10].…”
Section: Introductionmentioning
confidence: 99%
“…This study carefully analyzes how to instill the character of responsibility and selfconfidence in students through extracurricular activities outside conventional learning hours, specifically through drumband extracurricular activities in elementary schools. Responsibility is the attitude and behavior of individuals in fulfilling their duties and obligations towards themselves and other individuals in their environment [7]. When a person is able to balance responsibilities including his rights and obligations, it can have an impact on his confident character.…”
Section: Introductionmentioning
confidence: 99%
“…Extracurricular activities are all activities outside of 'classroom', such as involvement in university clubs, voluntary and paid work, family commitments, religious activities. Extracurricular activities are additional activities carried out by students outside of school hours, aiming to develop students' talents, JJPGSD P-ISSN: 2614-4727 E-ISSN: 2614-4735 abilities, interests, knowledge and abilities optimally, these activities are carried out at school and outside school to achieve educational goals (Puspitasari et al, 2021;Siregar et al, 2020;White et al, 2018). From the understanding that has been explained, it is concluded that extracurricular activities are activities that refer to activities fostered by adults such as associations held outside school hours, which have the aim of broadening experience, developing abilities, talents and interests of children (students) (Budi et al, 2020;Miftakhi, 2020;Yetti, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Various kinds of extracurricular activities in elementary schools which include sports, scouts, PMR, English club, arts and so on (Puspitasari et al, 2021;Rifa'i & Sunariya, 2020). One that is in great demand is extracurricular arts.…”
Section: Introductionmentioning
confidence: 99%